Minimal Residual Disease Detection and Evolved IGH Clones Analysis in Acute B Lymphoblastic Leukemia Using IGH Deep Sequencing - Wu, Jinghua; Jia, Shan; Wang, Changxi; Zhang, Wei; Liu, Sixi; Zeng, Xiaojing; Mai, Huirong; Yuan, Xiuli; Du, Yuanping; Wang, Xiaodong; Hong, Xueyu; Li, Xuemei; et al. (Frontiers in Immunology, 2016)
Acute B lymphoblastic leukemia (B-ALL) is one of most common types of childhood cancer worldwide and chemotherapy is the main treatment approach. Despite good response rates to chemotherapy regiments, many patients eventually relapse and minimal residual disease (MRD) is the leading risk factor for relapse. The evolution of leukemic clones during disease development and treatment may have clinical significance. In this study, we performed immunoglobulin heavy chain (IGH) repertoire high throughput sequencing (HTS) on the diagnostic and post-treatment samples of 51 pediatric B-ALL patients. We identified leukemic IGH clones in 92.2% of the diagnostic samples and nearly half of the patients were polyclonal. About 1/3 of the leukemic clones have correct open reading frame (ORF) in the complementarity determining region 3 (CDR3) of IGH, which demonstrates that the leukemic B cells were in the early developmental stage. We also demonstrated the higher sensitivity of HTS in MRD detection and investigated the clinical value of using peripheral blood in MRD detection and monitoring the clonal IGH evolution. In addition, we found leukemic clones were extensively undergoing continuous clonal IGH evolution by variable gene replacement. Dynamic frequency change and newly emerged evolved IGH clones were identified upon the pressure of chemotherapy. In summary, we confirmed the high sensitivity and universal applicability of HTS in MRD detection. We also reported the ubiquitous evolved IGH clones in B-ALL samples and their response to chemotherapy during treatment.